Analyzing the Factors Behind the Closure of “JoinB2B”: A Case Study of a B2B Marketing Communications Platform - Ibrahim Niftiyev (Proceedings of Tekirdağ Namık Kemal University Faculty of Economics and Administrative Sciences, II. International Symposium on Marketing, Tekirdağ / Türkiye, November 03-04, 2023, 2023)
The startup sector of Azerbaijan has developed rapidly and dynamically since 2014 and 2015, which should be considered a great success for the development of the non-oil industrial and service sector. However, systematic and in-depth studies on the performance of individual case studies have been neglected. Although this is understandable due to data constraints, limited access to businesses, and a non-liberal business environment, successful and failed startups should shed light on the most important aspects of growth management in the business sector. For this reason, this paper uses the in-depth interview method to collect data and analyze a specific case, namely “JoinB2B,” a startup company based in Hungary and Azerbaijan that made a failed attempt to build a global business-to-business marketing communications platform. The findings show that former co-founders and former employees agree that there were communication problems, misrepresentation of management, and issues with full dedication to the startup. This hindered the organizational development and maturity of the company. In addition, the COVID-19 outbreak exacerbated persistent communication gaps and created a chaotic situation. Former employees stated that the platform was not sufficiently improved to have adequate technical capacity, that a professional team of employees was never formed, and that there were still persistent problems with timing and planning to establish a locally and globally recognized brand. Finally, business experts and economists cited lack of capital, internal management problems, overestimation of the startup's ambitions, lack of a plan for business expansion and growth, and lack of state support and insufficient revenue raising as possible reasons for the closure. The study's findings are aimed at government agencies, research institutions, academics, and business experts, as academic research in this field is rare in Azerbaijan and should be encouraged.
Keywords: 330; Azerbaijan economy; business-to-business; case study; Hungary; marketing communications; startups